Hipokrisi, Munafiqin, Kafirin, Muttaqin - Sabillah, Indah (Jurnal Ushuluddin, 2021)
The aim of this research is to understand hypocrisy and to explore the interpretation of hypocrisy and its substance in Surah Al-Baqarah verses 8–20 in the Tafsir of Al-Jailani. In this study, the author employs a qualitative method using library research by examining and reading works relevant to the topic required for this research to ensure the accuracy of the findings. The results of this research show, according to the interpretation of Sheikh Abdul Qadir Al-Jailani, that a person who possesses the trait of hypocrisy is one who forgets the promises made in their original nature (fitrah) and always lives in pretense. Meanwhile, the substance of Surah Al-Baqarah verses 8–20 in Al-Jailani's tafsir explains that the disease of the heart, which attaches to a person who often lies about their faith, is characteristic of those who exhibit the traits of hypocrisy.